PANCASILA AS A BASIC GUIDELINE IN LEGAL PROTECTION OF HUMAN RIGHTS - Ibnu Abdillah; Nur Asyarah Tanjung; Aprilia Ayu Puspita; Anis Nur Aqilah (Academic Solution Publisher, 2024)
Human Rights are basic rights or citizenship that are inherent in individuals since they were born by nature which are given directly by God Almighty which cannot be taken away and revoked and must be respected, upheld, and protected by the state, law, government and every person for the honor and protection of human dignity and honor. Indonesia is a country based on law. So that the State of Indonesia is obliged to provide protection of Human Rights to every citizen. While a state of law is a country based on the sovereignty of law. The law is sovereign. The state is a legal subject, in the sense of rechtstaat. Because the state is seen as a legal subject, if it is guilty it can be prosecuted in court for unlawful acts. This study discusses the role of Pancasila as the basis of the state in protecting Human Rights (HAM) in Indonesia. With a qualitative approach and case studies, this study explores how the values ​​of Pancasila function as legal guidelines that guarantee the basic rights of citizens. Pancasila, although not explicitly mentioned in the 1945 Constitution, is a fundamental source of law that underlies legislation. The results show that the values ​​of Pancasila, especially